2006
DOI: 10.1164/rccm.200510-1648oc
|View full text |Cite
|
Sign up to set email alerts
|

Cell-specific Gene Expression in Patients with Usual Interstitial Pneumonia

Abstract: Altered gene expression of important profibrotic mediators in the different cellular lung compartments in patients with UIP likely plays an important role in pathogenesis of the deranged extracellular matrix deposition and subsequent fibrosis in this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…In a previous study also using LCM, in which only few MMPs were included, it was found that MMP-9 and MMP-7 were up-regulated in the epithelium adjacent to fibroblastic foci (33). MMP-1 and MMP-7 have been proposed as potential peripheral blood biomarkers in IPF (17), and MMP-7 increases in the plasma are predictive of significantly worse prognosis in IPF (34).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study also using LCM, in which only few MMPs were included, it was found that MMP-9 and MMP-7 were up-regulated in the epithelium adjacent to fibroblastic foci (33). MMP-1 and MMP-7 have been proposed as potential peripheral blood biomarkers in IPF (17), and MMP-7 increases in the plasma are predictive of significantly worse prognosis in IPF (34).…”
Section: Discussionmentioning
confidence: 99%
“…We, however, concern about false-positive immunohistochemical staining in Willis et al (2005), since there are a lot of granular staining in epithelial cells, quite unusual for smooth muscle actin. Recently, Kelly et al (2006) demonstrated that the expression of -SMA mRNA or protein was not detected in epithelial cells overlying Wbroblastic foci in IPF obtained by laser capture microdissection. It is possible that EMT is transient during some speciWc stage of Wbrogenesis, and we could not Wnd double positive cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies and immunohistochemical analyses have shown that IPF fibroblasts themselves are a significant source of many of these cytokines and chemokines, which can then act in an autocrine manner. Fibroblasts derived from IPF lungs are also characterized by dysregulated expression of metalloproteinases and their inhibitors [84], which likely contributes to the deranged tissue remodeling seen in IPF. In addition, they exhibit decreased ability to upregulate COX-2 expression, resulting in reduced production of prostaglandin E2 (PGE2), an inhibitor of fibroblast migration, proliferation, collagen production, and myofibroblast differentiation.…”
Section: Fibroblast Behaviormentioning
confidence: 99%